Digital image analysis allows objective stratification of patients with silent PIT1‐lineage pituitary neuroendocrine tumors - Jiangyan Zhao; Chenxing Ji; Haixia Cheng; Zhen Ye; Boyuan Yao; Ming Shen; Xuefei Shou; Xiang Zhou; Hongying Ye; Zhaoyun Zhang; Hong Chen; Yongfei Wang; et al. (The Journal of Pathology: Clinical Research, 2023)
Abstract Studies describing the clinical presentation and prognosis of patients with silent PIT1 (pituitary specific transcription factor)‐lineage pituitary neuroendocrine tumors (PitNETs) are rare. We identified patients with positive PIT1 tumor staining but without evidence of hormone hypersecretion at a tertiary center. Clusters were obtained according to cell morphology and immunostaining from each patient's digitally segmented whole slide image. We compared the clinical presentations, radiological features, and prognoses of the different clusters. We identified 146 patients (68 male, 42.9 ± 14.1 years old) with silent PIT1‐lineage PitNETs. Morphology clustering suggested that tumors with large nuclei and apparent eccentricity were associated with a higher proportion of aggressiveness and a higher hazard of recurrence [hazard ratio (HR): 2.64, (95% CI, 1.06–6.55), p = 0.037]. Immunohistochemical clustering suggested that tumors with thyroid stimulating hormone (TSH) staining or all negative PIT1‐lineage hormones were associated with a higher proportion of aggressiveness and a higher risk of recurrence [HR: 12.4, (95% CI, 1.60–93.5), p = 0.015]. We obtained three‐tier risk profiles by combining morphological and immunohistochemical clustering. Patients with the high‐risk profile presented the highest recurrence rate compared with those in the medium‐risk and low‐risk profiles [HR: 3.54, (95% CI, 1.40–8.93), p = 0.002]. In conclusion, digital image analysis based on cell morphology and immunohistochemical staining allows objective stratification of patients with silent PIT1‐lineage tumors. Typical morphological characteristics of high‐risk tumors are large tumor nuclei and high eccentricity, and typical immunostaining characteristics are TSH staining or negative staining for all PIT1‐lineage hormones.